Unilateral appearance of a chondro-epitrochlearis muscle-a case report - Jaijesh P (Indian Journal of Plastic Surgery)
Variant muscle slips from pectoralis major muscle are rare. Among these, the muscle chondro-epitrochlearis is a very rare muscular anomaly. Here, in this report, we describe a similar muscle which had an origin from the lower ribs along with the lower fibres of the pectoralis major muscle, arched across the axilla, and then inserted to the medial epicondyle of humerus. In this report we present a review of literature on this muscle. We also discuss the clinical significance of this muscle since the knowledge of this muscle is important in the differential diagnosis of ulnar nerve entrapment.